If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 6x = 2x + -32 Reorder the terms: 8 + 6x = -32 + 2x Solving 8 + 6x = -32 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + 6x + -2x = -32 + 2x + -2x Combine like terms: 6x + -2x = 4x 8 + 4x = -32 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + 4x = -32 + 0 8 + 4x = -32 Add '-8' to each side of the equation. 8 + -8 + 4x = -32 + -8 Combine like terms: 8 + -8 = 0 0 + 4x = -32 + -8 4x = -32 + -8 Combine like terms: -32 + -8 = -40 4x = -40 Divide each side by '4'. x = -10 Simplifying x = -10
| 1/2(x+8)=14 | | 4350-3915=87(50x-45) | | (x-3)/3=x/5 | | 11x+10=7x+2 | | 8x+3+5x-5=180 | | 35=10x+5y-15 | | x/8-5=-22 | | 9x+31x-9=8(5x+7) | | -3(t-2)+5t=4t-1 | | 10x+18=2x-2 | | 2x^2=x^3-x+1 | | 24x-5=6(4x+1) | | 12x-134=2x-14 | | 0.16d+0.6=.25(d-2) | | 14+a=2(a-0) | | 7x+23x-9=6(5x+1) | | 4n-31=13 | | 104x-104=13(8x-8) | | 4n+2=2n+1 | | 25x+70=25x+78 | | 14-3= | | 2x+x+3=7x-4x+3 | | (x+1)(x-1)(x-1)=0 | | 2z^2-162=0 | | 12+a=2(a-4) | | 3x+4x+1/7= | | 2(7t-4)=13 | | 7x+43x-9=10(5x+10) | | 4x+12x-6=4(4x+4) | | 34-2(x+3)=4x | | 3x+4x+4=19 | | 5+12=71+x |